2013
DOI: 10.1063/1.4793481
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate dependent mechanical properties in single crystal nickel nanowires

Abstract: Oxidation induced softening in Al nanowires Appl. Phys. Lett. 102, 051912 (2013) Layer thickness dependent tensile deformation mechanisms in sub-10nm multilayer nanowires J. Appl. Phys. 111, 124313 (2012) A fundamental numerical and theoretical study for the vibrational properties of nanowires J. Appl. Phys. 111, 124303 (2012) Note: Fast and reliable fracture strain extraction technique applied to silicon at nanometer scale Rev. Sci. Instrum. 82, 116106 (2011) Shape memory effects and pseudoelastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Driven by the electrical potential, Ni 2+ in the deposition solution was transported into the AAO channels and being further reduced into Ni atoms. With the confinement of AAO channels, Ni nanowires were finally formed with diameters determined by the channel diameters [43,44]. By tuning the deposition parameters such as temperature, AAO channel size, DC voltage and magnetic field, etc., these particular Ni nanowires with wire-axis-parallel nanotwin structures were successfully fabricated out (see Figure 1).…”
Section: Template-assisted Electrodeposition Of Nanotwinned Nickel Namentioning
confidence: 99%
“…Driven by the electrical potential, Ni 2+ in the deposition solution was transported into the AAO channels and being further reduced into Ni atoms. With the confinement of AAO channels, Ni nanowires were finally formed with diameters determined by the channel diameters [43,44]. By tuning the deposition parameters such as temperature, AAO channel size, DC voltage and magnetic field, etc., these particular Ni nanowires with wire-axis-parallel nanotwin structures were successfully fabricated out (see Figure 1).…”
Section: Template-assisted Electrodeposition Of Nanotwinned Nickel Namentioning
confidence: 99%
“…by fitting the curve of strain rate as a function of yield stress, as has been demonstrated for a screw dislocation motion in iron [35]. This problem will require a lot of computational efforts to model defects of different sizes, which is beyond the scope of the present paper.…”
Section: Effect Of Temperature and Strain Rate On The Pinning Strengtmentioning
confidence: 99%
“…To bridge the MD conditions and results with those of mechanical testing, the ratecontrolling deformation mechanism must be understood [34,35]. In the model of thermally activated dislocation motion, its velocity and the corresponding strain rate is given by [34]  …”
Section: Effect Of Temperature and Strain Rate On The Pinning Strengtmentioning
confidence: 99%
“…By combining a quantitative in-SEM nanoindenter, e.g., Refs. 9 and 10, and a micromechanical device, [11][12][13][14][15] with a sample preparation method that avoided surface modifications due to FIB milling, 6 the mechanical properties of Mo-alloy nanofibers with different initial dislocation densities were systematically investigated at different displacement rates. The average yield strength and its scatter were found to generally decrease with increasing pre-strain level at all three displacement rates.…”
mentioning
confidence: 99%
“…The fibers were then sonicated in order to break and separate them from the residual matrix and dispersed on a titanium-coated silicon wafer for subsequent manipulations onto a micromechanical testing platform. [11][12][13][14][15] Single crystal Mo-alloy nanofibers that were tested in this study all have a h100i growth direction as shown by the example in Figure 1(a). The dislocation densities in these nanofibers at several different pre-strain levels were carefully measured by Phani et al 18 using STEM imaging techniques.…”
mentioning
confidence: 99%